Group C Orthobunyavirus Infection in a Patient from the Amazon Putumayo Region of Colombia During an Oropouche Fever Epidemic - Sully Márquez; Lizeth Salazar; John Collins; Victoria Nipaz; Vanessa Dávila Campos; Jacob Van der Ende; J. Kenneth Wickiser; Thomas Briese; Josefina Coloma (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Orthobunyaviruses, one of the largest and most diverse genera of viruses, include numerous reassortant viruses and present diagnostic challenges due to similar clinical presentations with other arboviral infections. The detection and isolation of a group C orthobunyavirus from a patient with acute febrile illness from Puerto Ospina, Putumayo Department, Colombia during the 2023–2024 Latin American Oropouche fever regional outbreaks are reported in the present study. Using a vertebrate virus-focused metagenomics sequencing approach with VirCapSeq-VERT, a virus related to the Caraparu complex was identified, and a virus isolate was obtained. Although limited to a single case and without serological or longitudinal clinical confirmation, these findings underscore the value of unbiased molecular approaches for unresolved febrile illness diagnosis in endemic settings such as the Amazon basin.